Networks around Jasper von Munster. Teutonic Order during the Livonian War of Coadjutors in 1556 - Kreem, Juhan (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2015)
Livonian war of coadjutor’s broke out when the estates protested against the election of Christopher of Mecklenburg as a coadjutor of archbishop of Riga. At the same time, another conflict occurred, when Land Marshal of the Teutonic Order in Livonia, Jasper von Munster protested against the election of Wilhelm von Furstenberg as the coadjutor of the Livonian Master. As a result of the latter, Jasper was deposed and had to flee to Kaunas, from where he fought in vain for his restitution. This article aims first to identify and analyse the political network supporting Jasper inside of the Teutonic Order, and second to study the way the administrative network of the Order functioned during the conflict. It appears that Jasper’s political connections did not suffice to form his “party”, which could divide the chapter of the Order. During the conflict, the officials of the Order mostly retained their loyalty to the organization. Jasper was able to form a small retinue or a court of a kind, which consisted of local nobility, minor officials and even some fellow brethren of the Order, but it was not enough to confront the rest of the Order.